Banks' Lending Behavior and Firms' Corporate Financing Pattern in the People's Republic of China - Sayuri Shirati (Asian Development Bank Institute (ADBI), 2002)
This paper examines whether the banking sector reforms and equity market development have made any noticeable impact on banks lending behavior and firms corporate financing patterns in the Peoples Republic of China (PRC). Based on data on 1,098 publicly listed firms, it has been found that banks lending biases have been present especially toward large and less profitable firms and firms with greater State ownership throughout 1994-2000, and toward old firms during 1998-2000. Since most of these firms have been poorer performers than other firms, the results indicate the presence of a soft budget constraint. Moreover, this paper has also found that less profitable, large, and old firms have faced favorable lending bias after the initial public offerings (IPOs) on A-shares. The fact that these firms prefer bank loans over equity finance despite rising stock prices (hence lowering equity financing cost) suggests that banks either provided favorable financing conditions which may be due to collusion, or lack of borrowers incentive to diversify their financing sources. It is concluded that the banking sector reforms need to be strengthened further in order to improve their risk management skills and lower lending biases. On the other hand, lending bias towards firms with greater State ownership was also present, but the bias has declined after the IPOs. These firms seem to have increased greater recourse to total equity finance by issuing more non-negotiable shares than A-shares, probably to maintain management controls.
hdl:11540/4149
Keywords: 330; Kreditgeschäft; Bankenreform; Unternehmensfinanzierung; China